RF transparent vanadium oxide based single and bi-layer thin films as passive thermal control element for satellite antenna application. Issue 13 (September 2018) - Prajwal, K.; Carmel Mary Esther, A.; Dey, Arjun
Abstract: Germanium coated black polyimide (GBP) is often used as passive thermal control element for sunshield membrane of satellite antenna. However, GBP degrades fast while there is no protective coating applied. The present work is aimed towards the development of protective films which could hinder the degradation of GBP. At the same time, the basic characteristic of GBP membrane that is RF transparency should not be trade off. Here, RF transparent and protective vanadium oxide (VO) and vanadium oxide/silicon dioxide (VO/SO) thin films are developed by RF magnetron sputtering technique on GBP at a constant 400 W. Field emission scanning electron microscopy (FESEM) and X-ray photoelectron spectroscopy (XPS) techniques are utilized to investigate microstructural and oxide characteristics, respectively. Thermo-optical properties such as, solar absorptance (αs ) and IR emittance (εir ) are also evaluated. Introduction of SiO2 layer over vanadium oxide layer leads to decrease in αs to about 12%. RF losses e.g. insertion loss and return loss are measured in Ka band (27–39 GHz) and they found to be RF transparent characteristic. Thermal stability of the oxide films are also studied by differential scanning calorimetry (DSC) technique.